Dupilumab improves clinical symptoms in children with Netherton syndrome by suppressing Th2-mediated inflammation - Yan, Shi; Wu, Xuege; Jiang, Jinqiu; Yu, Shijuan; Fang, Xiao; Yang, Huan; Bai, Xiaoming; Wang, Hua; Luo, Xiaoyan (Frontiers in Immunology, 2022)
Background: Netherton syndrome is a rare, life-threatening autosomal recessive genetic disorder with no effective treatment yet. Skin barrier dysfunction caused by SPINK5 gene mutations is a hallmark of the disease. Antigen penetration through the defective skin and nonspecific inflammation provide a pro-T helper 2 immune microenvironment in the disease. Therefore, Th2 cytokines are considered to be candidate therapeutic targets. Objective: To evaluate the clinical responses of patients with Netherton syndrome to dupilumab, an IL-4Rɑ antagonist, and identify changes in the Th1/2/17 pathway activity, skin barrier defect protein LEKTI expression after treatment. Methods: Four children with severe Netherton syndrome (aged 2 y to 4 y and 6 m) treated with dupilumab from January to June 2022 were evaluated at baseline, and at 4, 8, 12, 16, and 20 weeks after the start of dupilumab administration. Treatment response was assessed using the Eczema Area and Severity Index, the Numerical Rating Scale, the Dermatology Life Quality Index, and the Dermatitis Family Impact-questionnaire. Blood eosinophil counts, serum IgE levels and inflammatory cytokines were measured. The immunotyping of Th1/2/17 cells was performed by flow cytometry and cytokine expressions in T cell subsets were analyzed by single-cell RNA sequencing. In addition, expression of the LEKTI in skin lesions was evaluated by immunohistochemical analysis. Results: All four patients experienced clinical improvement, with significantly reduced EASI scores and NRS from baseline to 20 weeks of treatment. Improved quality of life scores were also seen for all patients, as measured by CDLQI and DFI. Serum IgE levels also fell by 75.6–86.9%. The serum Th2 cytokines IL-4, IL-5 and IL-13 were found at low level, with no significant changes during the treatment. However, Th2 cytokines expressed by T cells, especially IL-4, decreased at single-cell level after treatment (P = 0.029). The baseline percentage of Th2 cells was significantly higher in patients than that in healthy controls (HC) (P < 0.0001). Conclusion: Dupilumab may be an effective and safe treatment option in a subset of pediatric patients with Netherton syndrome, especially in improving itch and the quality of life. These effects were achieved in part by suppression of the Th2-mediated inflammation.